Pug the Sports Star: Diary of a Pug #11 - May, Kyla ([Place of publication not identified] : Scholastic Inc., 2024)
Bub is a star with a basketball and a pug level hoop--but now Bella wants him to teach the other dogs the same trick, and Bub is not sure he wants to be in the spotlight.
new kids book 2024 fall.
Keywords: Pug; Basketball stories; Diaries; Dogs; Basketball; Diary fiction; Human-animal relationships; Juvenile fiction; Humorous fiction